Analisis Pendapatan Petani Karet Bibit Unggul Dan Bibit Tradisional Di Kecamatan Batang Cenaku Kabupaten Indragiri Hulu - Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2020)
AbstractThis research was conducted in the District of Batang Cenaku Indragiri Hulu. This is because the District of Batang Cenaku an area that makes rubber commodity as one commodity and in meeting their needs. The purpose of this study was to determine how the income of farmers in the district rubber rod upstream and Indragiri district Cenaku To know that used descriptive analysis, the data obtained are tabulated and then described by existing theories. The survey results revealed that the rubber plantation is vital to the income of the people in the District of Batang Cenaku Thus it can be seen that the average income of farmers quality seeds rubber plant samples with an area of 1 hectare of Rp. 8,241,724, - per year, while the average income of farmers' traditional seed samples rubber plant with an area of 2 hectares of Rp. 8,463,739, - per year. A comparison of income between farmers using traditional quality seeds and that happened 2 times where income 1 hectare equals income prefetch queue seeds 2 acres of farmers using traditional seeds.Businesses manage rubber plantation is a tradition for the people of District of Batang Cenaku Indragiri Hulu. Many efforts have been done by the government in the development of rubber plantations, such as by providing quality seeds and adequate capital for rubber farmers.